Alelopatia de extratos de adubos verdes no controle de plantas daninhas - Barbosa, Jaqueline de Araújo (2018)
The substances present in the plant material of green manures can act in the suppression of weeds by the release of allelopathic compounds. The objective of this study was to evaluate the allelopathic effect of the extracts of Dolichos lab lab, Pachyrhizus sp. and Sorghum bicolor, isolated and mixed, under different preparation method, in the weed species Bidens pilosa, Euphorbia heterophylla and Digitaria insularis. The experiment was realized in four stages, the collection of the vegetal material and the preparation of the aqueous extracts; influence of aqueous extracts on germination and initial development of B. pilosa, E. heterophylla and D. insularis, at completely randomized design was used, with factorial 7x4+T, and four replications; the effect of the aqueous extract were evaluated in post-emergence of B. pilosa, E. heterophylla and D. insularis, at completely randomized design was used, with six trataments and four replications, ermination and initial development of B. pilosa after the application of different fractions of aqueous extracts of D. lab lab, with dried plant material submitted to water bath, was used a completely randomized design with 14 trataments, ad four replications. In pre-emergence, the extract Pachyrhizus sp.+S. bicolor with freeze-dried plant material submitted to the water bath, reduced germination percentage, hypocotyl length and root length by 87%, 30% and 61%, respectively. For the E. heterophylla, the mixture Pachyrhizus sp.+S. bicolor, with freeze-dried plant material, caused the reduction of germianation percentage b 23%. For D. insularis, the extract Pachyrhizus sp.+S. bicolor, with freeze-dried plant material submitted to the water bath, reduced the percentage of germinations in 83%, and in 52% the length of the root. In post-emergence, the D. lab lab+Pachyrhizus sp. With freeze-dried plant material submitted to the water bath, reduced the dry mass of roots of B. pilosa plants by 21%, and by 18% the dry mass of roots of D. insularis, however, stimulated in 14% same variable in E. heterophylla. The fractionation of the D. lab lab extract with dried plant material, did not affect the germination percentage and dry mass of B. pilosa, but interfered the hypocotyl and the root. The fractionation of the D. lab lab + Pachyrhizus sp. + S.bicolor, with freeze—dried plant material submitted to the water bath, interfered in all variables. Is conclude that there is allelopathic effect of extracts of S. bicolor, D. lab lab, and Pachyrhizus sp. Isolated or in mixture, in different preparation method, on the germinability and development of B. pilosa, E. heterophylla and D. insularis, this stimulus os inhibition effect being according to the extract used and the method of preparation. Also, that the allelopathic effect happened by the action of several substances of different polarities.